2015
DOI: 10.1002/ange.201503362
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Enrichment of Volatile Iodine by Charged Porous Aromatic Frameworks with Three Sorption Sites

Abstract: The targeted synthesis of a series of novel charged porous aromatic frameworks (PAFs) is reported. The compounds PAF‐23, PAF‐24, and PAF‐25 are built up by a tetrahedral building unit, lithium tetrakis(4‐iodophenyl)borate (LTIPB), and different alkyne monomers as linkers by a Sonogashira–Hagihara coupling reaction. They possess excellent adsorption properties to organic molecules owing to their “breathing” dynamic frameworks. As these PAF materials assemble three effective sorption sites, namely the ion bond, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 41 publications
0
47
0
2
Order By: Relevance
“…Remarkably, TDPDB achieved the uptake capacity as high as 3.93 g g −1 , which is comparable with the adsorption capacity of similar polymer without methyl . As time went on, the color of TDPDB deepened from dark brown to the dark black at the end (Figure insert) . On the basis of the pore volume of TDPDB and the iodine density (pore volume in cm 3 g −1 × 4.93 g cm −3 ), the theoretical capacity of the TDPDB upon full occupation of its pore by iodine is 2.58 g g −1 , which is lower than its measured value.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Remarkably, TDPDB achieved the uptake capacity as high as 3.93 g g −1 , which is comparable with the adsorption capacity of similar polymer without methyl . As time went on, the color of TDPDB deepened from dark brown to the dark black at the end (Figure insert) . On the basis of the pore volume of TDPDB and the iodine density (pore volume in cm 3 g −1 × 4.93 g cm −3 ), the theoretical capacity of the TDPDB upon full occupation of its pore by iodine is 2.58 g g −1 , which is lower than its measured value.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, TDPDB can also adsorb iodine in organic solution. While a few TDPDB (20.0 mg) was immerged in an iodine‐cyclohexane solution (100 mg L −1 , 5.0 mL) in a small sealed bottle at 25°C, the iodine‐cyclohexane solution fades by degrees from purple to pale red with adsorption process prolonging (Figure S9), which indicated that iodine was adsorbed into the TDPDB network, successively producing iodine‐containing TDPDB network . Raman spectroscopy indicated that there are two forms of iodine, those are I 3 − (105, 146 cm −1 ) and I 5 − (165 cm −1 ) (green line in Figure S10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…但是, 核废料中的放射性核 物质(比如碘单质)的安全存储是影响核能应用的重 要 问 题 [75] . 通 过 选 择 带 电 荷 的 正 四 面 体 构 筑 单 元 LTIPB, 利用薗头偶联反应与四炔基四苯基甲烷合成 了新型荷电PAFs材料PAF-25 [76] . 新的具有硫脲基团的材料PAF70-thiourea [78] .…”
Section: 核能是非常重要的未来能源之一 只需消耗少unclassified
“…新的具有硫脲基团的材料PAF70-thiourea [78] . Progress of iodine release from PAF-25 when the containing iodine PAF materials were immersed in ethanol [76] 具有很高Pd固载量的PAF70-Pd, 该材料在铃木偶联 反应的过程中表现出了极高的催化活性(0.1 mg的催 化剂可以催化产出4.6 g的产品)和显著的择形性 [79] . 这些工作促进了介孔PAF材料的发展及其在催化和 其他领域的应用.…”
Section: 核能是非常重要的未来能源之一 只需消耗少unclassified